AKUNTABILITAS LEMBAGA OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN BANTEN DALAM MENANGANI LAPORAN MALADMINISTRASI - Tika Febriani Putri; Nikki Prafitri (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
Accountability is the obligation to provide accountability or answer and explain the performance and actions of a person/legal entity/leader of an organization to a party that has the right or authority to request such information or accountability. In the implementation of public services in Banten Province there are still many acts of maladministration, this can be seen from the reports of complaints submitted to the Ombudsman Representative of Banten. However, in practice the Banten Representative Ombudsman still encountered obstacles, namely the unresolved report on alleged maladministration for 2022, and the lack of human resources in the Banten Representative Ombudsman so that the Ombudsman was not optimal in handling reports. The purpose of this research is to find out and analyze the Accountability of the Ombudsman Institute of the Republic of Indonesia Banten Representative in Handling Maladministration Reports. The method used in this study is qualitative with a purposive selection of informants. The theory used is accountability dimensions according to Koppell, namely: transparency, liability, controlability, responsibility, and responsiveness. Data collection techniques by observing, interviewing and documentation. Testing the validity of the data using triangulation and member checks. The results of this study are that the Ombudsman of the Republic of Indonesia Representative of Banten in handling reports of maladministration is not optimal. This is indicated by the lack of access to information provided by the Ombudsman Representative of Banten in viewing the results of their performance, as well as the lack of human resources in the process of resolving maladministration reports.